The association between depression and length of stay in the intensive care unit - Liao, Kuang-Ming (Medicine (Baltimore), 2020)
Depression is common after patients are discharged from the intensive care unit (ICU) and has a negative impact on quality of life and mortality. There is inconsistent information about ICU admission and the risk of depression. The aim of our study was to investigate the association between the risk of depression and length of ICU stay. ICU survivors between 20 and 65 years old were enrolled in this study using data from Taiwan's nationwide population database. All study subjects were followed for a maximum of 1 year or until they were diagnosed with new-onset depression. The association between the length of ICU stay and the depression risk among ICU survivors was estimated using a Cox regression model. The screened diagnostic records of ICU survivors with depression were also investigated to find the potential disease effect of depression. Compared to patients with ICU stays between 8 and 14 days, the adjusted HR (95% confidence interval) for depression in patients with ICU stays between 1 to 3 days, 4 to 7 days, 15 to 21 days, and ≥22 days were 1.08 (1.03–1.13), 1.01 (0.96–1.05), 1.08 (1.01–1.14), and 1.12 (1.06–1.19), respectively. For patients with depression after discharge from the ICU, the most common primary diagnosis was intracerebral hemorrhage. There is a risk of depression after ICU discharge, and the incidence of depression may be higher among patients between 20 and 49 years old. The risk of depression was U-shaped, with higher risks associated with ICU stays of 1 to 3 days and more than 15 days.